Studies on the level of awareness and social acceptance of herbal biscuits in Sri Lanka - Nayanajith, R.P.D.N; Vasantharuba, S.; Dharmasri, P.G.N.H. (University of Jaffna, 2022)
A biscuit is one of the typically baked snacks consumed in Sri Lanka. This study examined the awareness and social acceptance of different types of herbal biscuits available in the Sri Lankan market. Information about the available herbal biscuits on the local market was acquired with the help of a questionnaire survey designed using the Google form, and 135 participants participated island-wide. The participant age groups were categorized from twenty to over forty-one. The 20−25 years age group was taken by the majority with 57.7 % of the 135 participants. Results of the studies showed that female participants (69.2 %) significantly outnumbered male participants (30.8 %). Out of 135 respondents, 81.5 % preferred to consume biscuits. The taste (55.3 %) and easy accessibility (46.5 %) of biscuits are the critical reasons for their preference. This study showed that most Sri Lankans select their biscuits based on the popularity of the brands. Among the ten different varieties of biscuits utilized in this survey, cookies (42.2 %) and regular biscuits (37 %) are the two most popular categories. Of the participants, 75.4 % tried the herbal biscuit, while 24.6 % had never tried it. Herbal biscuits are consumed rarely (38 %), followed by once a month (24 %) and once a week (18 %) by the respondents. Herbal biscuits fortified with ginger (74.8 %) and curry leaves (50.4 %) are the most popular types among consumers. The majority of customers (68.89 %) purchased herbal biscuits because of their health benefits. Most consumers (68.89 %) purchased herbal biscuits due to their health impacts. The levels of sugar, salt and fat are around 46.3 % and fortified ingredients are around 44.8 % which are the most important factors when purchasing the herbal biscuits for the participants. Results of the survey showed that most of the respondents (47.8 %) thought that the price range of the herbal biscuit was affordable. Most respondents (63.7 %) believe that herbal biscuits can provide additional vitamins to consumers. According to the findings of this study, herbal cookies are recommended for adults who need to improve their health status.
Keywords: Fortification; Herbal biscuits; Respondents; Survey